Post-translational modifications of ezrin: a crucial regulator for diseases - Yi-Chen Li; Hong-Kai Yuan; Lei-Miao Yin (Amino Acids)
Abstract Ezrin is a crucial structural protein that connects the plasma membrane to the actin cytoskeleton to maintain cell shape, adhesion, and motility. Post-translational modifications (PTMs) play a key role in the regulation of various biological functions and have been implicated in a range of pathological conditions. With the help of PTMs, ezrin not only plays a structural role in connecting the cell membrane to F-actin, but also participates in transmitting cellular signals including those related to inflammatory responses. In this study, we reviewed the key sites and domains involved in the different PTMs of ezrin, including acetylation, lactylation and phosphorylation. We analyzed the regulation of biological processes mediated by different PTMs of ezrin, such as cell migration, inflammation regulation and cell stiffness. In addition, we examined the mutual regulatory effects of different modifications of ezrin, including regulation of ezrin phosphorylation by kinases and phosphatases, and so on. Increasing evidence suggests that PTMs of ezrin are involved in cancer, respiratory diseases and urological diseases. These studies provide novel insights into the design of new disease treatment strategies targeting ezrin.